A genealogy of terrorism: colonial law and the origins of an idea - McQuade, Joseph (Cambridge University Press, 2021)
Using India as a case study, Joseph McQuade demonstrates how the modern concept of terrorism was shaped by colonial emergency laws dating back into the nineteenth and early twentieth centuries. Beginning with the 'thugs', 'pirates', and 'fanatics' of the nineteenth century, McQuade traces the emerging and novel legal category of 'the terrorist' in early twentieth-century colonial law, ending with an examination of the first international law to target global terrorism in the 1930s. Drawing on a wide range of archival research and a detailed empirical study of evolving emergency laws in British India, he argues that the idea of terrorism emerged as a deliberate strategy by officials seeking to depoliticize the actions of anti-colonial revolutionaries, and that many of the ideas embedded in this colonial legislation continue to shape contemporary understandings of terrorism today.